The Concept of “Manguurt” In Ethnography and its Literary Transformation - Shokankhan, Kuttybayev; Yedilbay, Ospanov; Balkiya, Kassym; Aiman, Koblanova; Bakytgul, Moldagali (Journal of Ecohumanism, 2024)
This article analyzes the idea of “Manguurt” in Aitmatov’s works, comparing it to historical events in Central Asia and the world, as well as to similar themes in global literature. Aitmatov’s “Manguurt” concept carries a profound philosophical meaning. By giving a new meaning to this term, Aitmatov highlights the inner cries of the Central Asian peoples who were part of the former Soviet Union. Their inherent self-awareness, distinctive language, and traditions were swallowed up by the red empire, turning them into a nation with a bleak future. This resulted in the formation of a generation that put Soviet ideology above the interests of its own people.